Gender and performance disparity in mathematics: A study of South Western Uganda - Amos, Musimenta; Francis Akena, Adyanga; Denis, Sekiwu (African Educational Research Journal, 2020)
Gender has long been considered a factor contributing to differences in performance for male and female students in diverse educational disciplines and levels. Although male and female students are taught in the same classrooms in most Ugandan schools, there have been noticeable differences in Mathematics performance in national examinations across the country. Thus, the aim of this study was to compare male and female students’ performance in Mathematics and to establish factors accounting for the differences. Using the Mixed method design, a sample size of 222 participants was recruited. The major findings revealed that variation in Mathematics performance cannot be attributable to gender. The study deconstructs the common gender-biased assumption that girls are naturally a ‘weaker sex’ and hence likely to embrace subjects that are considered ‘soft’ such as language, literacy, communication skills, social sciences among others. Such assumptions commonly fronted inadvertently without considering possible negative consequences, are based on societal construction of social differences with no substantive evidence as demonstrated in this study.